1999
DOI: 10.1002/hep.510290224
|View full text |Cite
|
Sign up to set email alerts
|

Detection of occult low-grade B-cell non-hodgkin's lymphoma in patients with chronic hepatitis C infection and mixed cryoglobulinemia

Abstract: Hepatitis C virus (HCV) is both hepatotropic and lymphotropic and has been shown to be associated with the benign lymphoproliferative disorder, mixed cryoglobulinemia (MC). Preliminary studies suggest that there may be an association between chronic hepatitis C, MC, and non-Hodgkin's lymphoma (NHL). The aim of this study was to determine whether patients with chronic HCV and MC have occult bone marrow NHL. Sixteen patients with chronic HCV and clinically active MC underwent bone marrow biopsy and aspiration. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(41 citation statements)
references
References 14 publications
0
40
0
1
Order By: Relevance
“…Five of these cases had grade II and two had grade III MALT lymphoma. This result suggests that HCV may permit the development of acquired MALT [40]. In another study, flow cytometry of bone marrow aspirates was used to study 16 cases having chronic HCV infection with clinically active mixed cryoglobulinemia, and NHL was detected in 2 cases [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five of these cases had grade II and two had grade III MALT lymphoma. This result suggests that HCV may permit the development of acquired MALT [40]. In another study, flow cytometry of bone marrow aspirates was used to study 16 cases having chronic HCV infection with clinically active mixed cryoglobulinemia, and NHL was detected in 2 cases [41].…”
Section: Discussionmentioning
confidence: 99%
“…Infection of peripheral blood mononuclear cells with HCV is a useful parameter in the pathogenesis of HCV infection [40]. Although some investigators believe HCV plays a role in the pathogenesis of NHL, some others refuse this explanation [8,9,25,26,30,[43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…61 Persistence or relapse of CV even after clearance of HCV infection should make one suspect and rule out B cell malignancy as B cell lymphomas have been reported in such cases. 62 Most anti-inflammatory drugs used for management of other vasculitides like cyclophosphamide have been used for management of CV. However, it has been shown that immunosuppressive treatment has been associated with increased mortality independent of disease activity.…”
Section: Management Of Mixed Cryoglobulinemiamentioning
confidence: 99%
“…5 Mixed cryoglobulinemia is considered by some investigators to be a variant of lowgrade, B-cell non-Hodgkin's lymphoma. 6,7 This has prompted several groups to investigate the association between HCV infection and overt B-cell malignancies. Evidence suggesting a direct relationship between HCV infection and development of these tumors have been reported in several Italian studies and in one American study, which demonstrates a high prevalence of chronic HCV infection, 9% to 42%, in patients with B-cell lymphoma.…”
Section: H Epatitis C Virus (Hcv) Is a Hepatotropic Virus;mentioning
confidence: 99%